“SUSTAINABLE DEVELOPMENT” AS THE MODERN OBJECTIVE OF ENGINEERING EDUCATION - Vyacheslav M. Prikhodko (Высшее образование в России)
In this paper we propose to consider the purpose of engineering education as opportunities to improve the quality of humankind’s life (in the framework of «sustainable development»). It is proposed coordination of teacher training at the Centers for Engineering Education IGIP for this purpose, as well as the need to address this preparation to the problems of engineering education in Russia.